Sustainability and Conserved Energy Value of Heritage Buildings - Dalia Elsorady (Renewable Energy and Sustainable Development, 2017)
Conservation and sustainability have long shared fundamental goals. Heritage buildings are basically sustainable and will continue to be if their sound construction and superior materials are conserved properly. Despite this fact, heritage buildings have gained a reputation for being inefficient and therefore unsustainable in the face of modern, energy-efficient structures. As a result, models which are measured embodied energy arose to advocate the retention of heritage structures over new constructions. The initial need to measure energy capital in buildings started due to rising needs to save energy and address global sustainability goals. Both responses measure overall energy efficiency of heritage buildings by attempting to account for the "energy capital." The life cycle assessment/avoided-impacts model is another model that acts as a response to the evolving metrics and currency of sustainability. The Conservation Green Lab has further developed the capabilities of the life cycle assessment/ avoided impacts model in 2012  in its innovative report: “The Greenest Building: Quantifying the Environmental Value of Building Reuse”. With this aim, the study applies energy software models supported by guidelines laid out by LEED, and are consistent with judicious conservation practice on a case study heritage building in Alexandria. The outcome revealed proves that heritage buildings can be both sustainable and energy efficient while maintaining their historic integrity, when dealt with properly.